Respuestas

  • Usuario de Brainly
2013-11-19T22:47:11+01:00
1)

F(x) =  ln ( x √x² + 1)

F(x) = ln ( x.x + 1)

F(x) = ln (x² + 1 )

Derivando:                

Aplicamos propiedad:  d(ln(u))/dx = (1/u) . du/dx

F'(x) = 1/(x²+1)  . [x²+1]'
F'(x) = [ 1/(x²+1) ][2x]
F'(x) = 2x/(x²+1)     Respuesta

2)

F(x) = e - xln x

Derivando:

F(x) = (e)' - (xlnx)'

Como : e = 2,71828....  , entonces:

F(x) = 0 - [  (x)'.lnx +  x.(lnx)' ]

F(x) =  - [ lnx + x(1/x) ]

F(x) = - [ lnx + 1]

F(x) = -lnx -1      Respuesta.